Thoughts on the Importance of a Migrant Health Database in Connection with the Asylum Crisis of 2015 on the Occa- sion of the Consensus Conference - Szijártó, István (Pécs journal of international and European law, 2019)
The article examines public health issues related to the asylum crisis of 2015 in the European Union. It does so by first reviewing the Consensus Conference held in Pécs on the 8-9th October 2019. It examines legal aspects of creating a migrant health database on a European level consist- ing of health data of migrants and asylum-seekers in order to tackle public health risks brought by the mass influx of refugees. As a final point, the article suggests two possible ways to incorporate the migrant health database to the reform of the Common European Asylum System.